On the Relationship of Interoceptive Accuracy and Attention: A Controlled Study With Depressed Inpatients and a Healthy Cohort - Schultchen, Dana; Schneider, Carolin; Berberich, Götz; Zaudig, Michael; Erle, Thorsten M.; Pollatos, Olga (Frontiers in Psychology, 2021)
Objective: Previous research has shown reduced interoceptive accuracy (IAcc) in depression. Attention deficit represents a key symptom of depression. Moreover, IAcc is positively correlated with attention. There is no study investigating the effect of depression on IAcc and attention. The aim of the study is to investigate the mediating effect of IAcc on depression and attention. Methods: 37 depressed patients from the Psychosomatic Clinic in Windach were matched with 37 healthy controls in age and sex and assessed at Ulm University. All participants completed the Beck Depression Inventory-II, the heartbeat perception task to examine IAcc, and the d2 test assessing selective attention. Results: Depressed patients showed attention deficits – both for general visual attention and IAcc – compared to healthy controls. The mediation analyses revealed that the relationship between depression and attention isn’t mediated via IAcc. Furthermore, depression predicts IAcc and attention, but these effects are direct and largely unaffected by the respective other variable. Discussion: The results of the present study highlight both interoceptive as well as attention deficits in depressed patients. No clear mediation between these variables could be shown in this study. More elaborative research is needed to clarify whether different approaches to improve IAcc are effective for these deficits in depressed patients and could therefore be of importance as additional therapy aspect in depression.